Choroidal metastasis response to crizotinib in a ROS1-rearranged NSCLC patient. Issue 2 (February 2015) - Lu, Stephanie; Azada, Michele C.; Ou, Sai-Hong Ignatius
Abstract: Objectives: Choroidal metastases are uncommon metastasis from non-small cell lung cancer (NSCLC). With improved survival from the use of targeted therapy against actionable driver mutation driven NSCLC, the incidence of choroidal metastases seems to be increasing. Recently, there are several case reports of choroidal metastases in patients with anaplastic lymphoma kinase ( ALK )-driven NSCLC one of which the patient's choroidal metastases had responded to crizotinib, multi-targeted tyrosine kinase inhibitor against ALK/ROS1/MET. Similarly ROS1 -rearranged NSCLC has very similar clinicopathologic characteristics as ALK -rearranged NSCLC and crizotinib has demonstrated significant clinical activity against ROS1 -rearranged NSCLC. Materials and methods: Here in this report we presented a patient with ROS1 -rearranged NSCLC that presented with choroidal metastases that did not respond to initial chemotherapy but had a rapid and complete response to crizotinib. Conclusions: Although likely to be exceeding rare, choroidal metastases from ROS1 -rearranged NSCLC can be successfully treated with crizotinib similar to choroidal metastases from ALK -rearranged NSCLC can be successfully treated from another case report.